Influence of tillage and mulching on the growth and yield of rainfed wheat (Bangladesh Journal of Agricultural Research, 2008)
Field experiments were conducted at the Regional Agricultural Research Station of the Bangladesh Agricultural Research Institute (BARI), Jessore during the rabi seasons of 1999-2000 and 2000-2001 to evaluate the effect of different tillage and mulch practices on the conservation of residual soil moisture, yield attributes, and yield of wheat (cv. Shatabdi). The experiment consisting of three levels of tillage viz., minimum, reduced, and conventional tillage and four levels of mulch viz., rice straw, water hyacinth, black polythene, and no mulch. The experiment was laid out in a split-plot design distributing the tillage treatments to the main plots and mulches to the sub-plots. Yield and yield components of wheat were significantly influenced by tillage practice. Reduced tillage gave consistently the highest grain yield and the lowest grain was obtained from minimum tillage in both the years. Black polythene mulch significantly increased grain yield by 29% over no mulch and also conserved more moisture in the soil. Variation in yield was also noticed between years, higher yield being in 2000-2001 than in 1999-2000 which can be explained by higher soil moisture for rainfall (189 mm) occurring in 2000-2001. Two years' results indicated that polythene mulch or rice straw mulch accompanied by reduced tillage might be an efficient practice in order to conserve soil moisture for higher yield of wheat under rainfed condition.Bangladesh J. Agril. Res. 32(4) : 649-661